Using the Chinese version of Memorial Delirium Assessment Scale to describe postoperative delirium after hip surgery - Shi, Zhongyong; Wu, Yujie; Li, Cheng; Fu, Shukun; Li, Guodong; Zhu, Yingbo; Swain, Celeste A.; Marcantonio, Edward R.; Xie, Zhongcong; Shen, Yuan (Frontiers in Aging Neuroscience, 2014)
Objective: Memorial Delirium Assessment Scale (MDAS) assesses severity of delirium. However, whether the MDAS can be used in a Chinese population is unknown. Moreover, the optimal postoperative MDAS cutoff point for describing postoperative delirium in Chinese remains largely to be determined. We therefore performed a pilot study to validate MDAS in the Chinese language and to determine the optimal postoperative MDAS cutoff point for delirium. Methods: Eighty-two patients (80 ± 6 years, 18% male) who had hip surgery under general anesthesia were enrolled. The Confusion Assessment Method (CAM) and Mini-mental state examination (MMSE) were administered in the patients before surgery. The CAM and MDAS were performed in the patients on the first, second, and fourth postoperative day. The reliability and validity of the MDAS were determined. Receiver operating characteristic (ROC) curve was used to determine the optimal Chinese version MDAS cutoff point for the identification of delirium. Results: The Chinese version of the MDAS had satisfactory internal consistency (α = 0.910). ROC analysis obtained an average optimal MDAS cutoff point of 7.5 in describing the CAM-defined postoperative delirium with an area under the ROC of 0.990 (95% CI 0.977-1.000, P < 0.001). Conclusions: The Chinese version of MDAS had good reliability and validity. The patients whose postoperative Chinese version of MDAS cutoff point was 7.5 would likely have postoperative delirium. These results have established a system for a future larger scale study.